Improved analytical method to study the cup anemometer performance. (15th September 2015) - Pindado, Santiago; Ramos-Cenzano, Alvaro; Cubas, Javier
Abstract: The cup anemometer rotor aerodynamics is analytically studied based on the aerodynamics of a single cup. The effect of the rotation on the aerodynamic force is included in the analytical model, together with the displacement of the aerodynamic center during one turn of the cup. The model can be fitted to the testing results, indicating the presence of both the aforementioned effects.